A new species of Crenitulus Winters, 1926 (Coleoptera: Hydrophilidae: Chaetarthrinae: Anacaenini) from northern South America - Santana, Larissa; Benetti, Cesar João; Pes, Ana Maria (Zootaxa, 2017)
A new species of the genus Crenitulus Winters, 1926 (Hydrophilidae: Chaetarthrinae: Anacaenini), C. clarksoni sp. nov. is described from northern Brazil and Guyana. The new species can be distinguished from other species of Crenitulus by the following combination of characteristics: body size 1.6–1.8 mm in length; clypeus, frons, pronotum and elytra black, pronotum with distinctly demarcated yellow lateral margins; presence of dorsal pubescence and longitudinal rows of coarser punctures on lateral margins of elytra; apical antennomere 1.5 times longer than wide and 2.5 times longer than antennomere 8; maxillary palpi 2.5 times longer than wide and 2.2 times longer than palpomere 3; mesoventrite nearly flat; procoxae with strong, large spines; femoral pubescence confined to anterior margin and proximal portion; by phallobase as long as parameres; by parameres narrowed apically with the apex rounded and by the median lobe slightly shorter than parameres with corona in subapical position.